(untitled) (Thành phố Hồ Chí Minh, 2014)
Book 3 - Advanced Level is the final book in a range of three graded vocabulary books, and builds on the Foundation Level book to deliver the essential vocabulary students need to succeed in the IELTS exam. The Advanced Level book covers the harder vocabulary that may appear in the exam, and that students may need to master to achieve the scores required by most universities and employers. It covers advanced-level words and phrases from the Academic Word List, and includes thematic vocabulary-building sections, organized according to topics that frequ
Keywords: Vocabulary,Từ vựng,English language,Ngôn ngữ Anh